Influenza Vaccine Uptake and Associated Factors in Aged Care Facilities. Issue Volume 34:Issue s1(2019) (May 2019) - Kunasekaran, Mohana; Trent, Mallory; Lai, Elisa; Tan, HaoYi; Chughtai, Abrar; Poulos, Chris; MacIntyre, Raina
Abstract : Introduction: Influenza vaccine is recommended for high-risk populations in Australia (including those aged over 65 years) but is less effective in the elderly due to a progressive and predictable age-related decline in immune function, referred to as immunosenescence. Aged care facilities (ACF) are known to be at high risk of explosive outbreaks of influenza (even in highly vaccinated populations) and may reflect a higher intensity of transmission within the closed setting of ACF, as well as lower immunity and immunosenescence in the frail elderly. Methods: To measure the impact of influenza in aged-care staff (ACS) and residents as well as vaccine effectiveness, a prospective observational epidemiological study was conducted in collaboration with an aged-care provider with multiple sites from March to October 2018. Weekly active surveillance on influenza-like symptoms and questionnaires were used to collect data on two groups: ACS and residents. A range of variables was examined against their 2018 influenza vaccination status in statistical analysis. Results: Vaccination rates were high in residents and consistent with other studies. Vaccine rates in aged-care staff were lower and consistent with other studies. Discussion: Residents and relatives are unlikely to change their minds about vaccination from year to year unless there is targeted effort to persuade them to so, and negative perception of the vaccine is likely to persist. Workplace influenza vaccination programs targeted at staff could be an effective method of raising vaccine uptake.